El juego de la sombra - Erdrich, Louise (Nuevos tiempos (Madrid, Spain), 2012)
This novel presents the story of Irene America, who is a smart, beautiful, introspective woman of Native American decent. Too distracted to finish her doctoral degree, she musters the emotional resources needed to keep two journals. The "Red Diary" is bait, filled with adulterous scenes that Irene uses to push volatile artist husband Gil close enough to the brink that he'll leave her. She unleashes all her rage and frustration in the "Blue NoteBook," which she keeps in a bank deposit box. Meanwhile, Gil believes that his obsessive graphic paintings of Irene will somehow lure her back to him. Caught in the crosshairs of their parents' cruel, messy unraveling are 13-year-old Florian, a genius who models his mother's excessive drinking habits; Riel, 11, who believes that only she can hold her disintegrating family together; and sunny little Stoney. The result is a cautionary tale of the shocking havoc that willfully destructive, self-centered spouses wreak not only upon themselves but also upon their children.